Comparison of methods and tools for generating levels of details of 3D models for popular game engines - Tomecki, Michał (Journal of Computer Sciences Institute, 2020)
Computer games have come a long way since their inception using increasingly advanced graphics. With so many models present on the screen at the same time, simplified models are needed that will be replaced when they are further away from the camera in the game. The aim of the study was to compare the tool for automatic generation of model detail levels in Unity and Unreal Engine. The article presents the results of the equipment load test and the time needed for generation, as well as a survey checking the opinion of people.